Polymer Concentration and Solvent Variation Correlation with the Morphology and Water Filtration Analysis of Polyether Sulfone Microfiltration Membrane. (3rd March 2019) - Alvi, Muhammad Azeem U. R.; Khalid, Muhammad Waqas; Ahmad, Nasir M.; Niazi, Muhammad Bilal K.; Anwar, Muhammad Nabeel; Batool, Mehwish; Cheema, Waqas; Rafiq, Sikandar
Abstract : Microfiltration flat sheet membranes of polyether sulfone (PES) were fabricated by incorporating varying concentrations of polymer and investigated the influence of substituting solvents. The membranes were prepared via immersion precipitation method. Different solvents that included NMP (N-methyl-2-pyrrolidone), DMF (dimethylformamide), and THF (tetrahydrofuran) were used to analyse their effect on the performance and morphology of the prepared membranes. Two different coagulation bath temperatures were used to investigate the kinetics of membrane formation and subsequent effect on membrane performance. The maximum water flux of 141 ml/cm 2 .h was observed using 21% of PES concentration in NMP + THF cosolvent system. The highest tensile strength of 29.15 MPa was observed using membrane prepared with 21% PES concentration in NMP as solvent and coagulation bath temperature of 25°C. The highest hydraulic membrane resistance was reported for membrane prepared with 21% PES concentration in NMP as solvent. Moreover, the lowest contact angle of 67° was observed for membrane prepared with 15% of PES concentration in NMP as solvent with coagulation bath temperature of 28°C. Furthermore, the Hansen solubility parameter was used to study the effect on the thermodynamics of membrane formation and found to be in good correlation with experimental observation and approach in the present work.